Intelligent Reconfigurable surface technique for Multiple Antenna Communication System - Noor Qasim; Ismail Hburi; Haider Salih Al Ammar (Wasit Journal of Engineering Sciences)
The throughput growth of the coming wireless communication schemes requires the deployment of more base stations at a lower power use. We were inspired by the newly recommended intelligent reconfigurable surface technique (IRS) to address this issue. Specifically, this article mainly concerns the joint pre-coding scheme design challenge concerning improving the output at the base station (or the access point) and IRS stages. An iteration strategy called MMSE-MP has been developed, procedures a minimum mean squared error pre-coder (MMSE) approach for the Digital-BF and the Matching Pursuit (sparse approximation algorithm) for the Analog pre-coding, to cope with this complex challenge. For the reflecting element phase shift matrix the algorithm uses the arrival/departure angles of the LoS rays at the IRS elements. Basically, the joint problem of optimizing the analog and the digital pre-coder was transformed into a one-variable matrix reconstruction, i.e., sparsity-constrained signal-recovery optimization. The simulation outcome confirms that there is nearly 66.5% spectral enhancement if comparing with the classic network without IRS for a certain power scenario of the scheme.